2014
DOI: 10.1080/03630242.2014.897674
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Sexual Violence and Sexual Problems Among Gynecology Outpatients: An Example from Turkey

Abstract: Domestic violence is a universal problem, and sexual violence in marriage, in particular, is a hidden form of it. This descriptive, cross-sectional study was conducted to determine to the prevalence of domestic sexual violence by husbands, the prevalence of sexual problems, and the relation of these among married women attending a gynecology outpatient clinic. This study was performed in a university hospital in Turkey and data were collected February-April 2009. The study sample consisted of 200 married women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…Sexual violence is a type of domestic violence and mostly emerges in marriage or intimate partnership scenarios [6]. Sexual violence against women and intimate partner violence is a problem that has a serious impact on the health and welfare of a great number of women from all around the world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual violence is a type of domestic violence and mostly emerges in marriage or intimate partnership scenarios [6]. Sexual violence against women and intimate partner violence is a problem that has a serious impact on the health and welfare of a great number of women from all around the world.…”
Section: Introductionmentioning
confidence: 99%
“…As an effect of tradition and religious norms in Turkey, it is believed that violence, sexuality, and similar domestic matters should be immune to intervention. Since women widely hold the belief that, in marriage, the sexual needs of men must be met, they do not consider acts of sexual violence as criminal acts and never speak openly about these acts anywhere, let alone to judicial authorities [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the study conducted by Hastuti et al on women of reproductive age in Indonesia, it was indicated that women who experience intimate partner violence were four times more likely to show sexual dysfunction [13]. In addition, Ipekten Alaman and Yildiz in Turkey reported that women who experience IPV show more sexual dysfunction, and suffer specially from orgasm disorder [39]. In Iran, Jamali et al showed that increased IPV led to sexual dysfunction [14].…”
Section: Discussionmentioning
confidence: 99%
“…Results of their study comply with the results of the present study. Ipekten Alaman and Yildiz reported that when women were passive in terms of sexuality or when their husbands were not sexually satisfied, their husbands violence behaviors increased, and women expressed that they occasionally had sexual intercourse unwillingly since they were afraid of their spouse's violent reactions [39]. In general, the inability to respond sexual needs plays an important role in the couple's dissatisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Evlilik içi cinsel saldırılarda diğer cinsel saldırılara göre bu oranın daha da düşük olduğu bildirilmiştir (4,5). Başvuru yapan olguların adli tıp açısından özel olduğu düşünülmektedir.…”
Section: Introductionunclassified